Cross-border Electricity Transfers in the case of differentiated Renewable Energy Sources: A Simulation Analysis for Germany and Spain - Andreas Coester; Marjan Hofkes; Elissaios Papyrakis (Tinbergen Institute, 2022)
Renewable electricity plays an increasingly important role in the effort to reduce CO2 emissions in the electricity sector. One of the major challenges that must be addressed is the fluctuating supply of renewable electricity. We explore the impact of cross-border electricity transfers on both the security of electricity supply and renewable electricity expansion. We focus on Spain and Germany due to the relative abundance of their country-specific renewable electricity sources (solar for Spain and wind for Germany). We develop an electricity market model that allows for cross-border electricity transfers by connecting country-specific electricity markets. We apply six policy scenarios aiming towards securing the electricity supply and renewable electricity expansion. Our simulation results show that cross-border electricity transfers postpone supply shortages in both countries. These shortages occur as a result of an increasing amount of low-marginal-cost renewable electricity, which, in turn, leads to a decrease in the electricity price, so that power plants cannot operate profitably. However, the postponement of these supply shortages is primarily achieved through an excess supply of German conventional power plants that are utilised to meet excess demand in Spain. Although this serves to reduce required government subsidies, it also leads to an increase in CO2 emissions.
Keywords: Q41; Q42; Q48; 330; Cross-border electricity transfers; Security of electricity supply; Renewable Electricity